Journal: 100 Years / FIG. 2. Bridge wrecked by material from blast near Chattanooga, Tenn - Robert Hopler (International Society of Explosives Engineers, 2008)
A blast caused the destruction of a bridge and loaded freight train and the death of three men, near Chattanooga, Tenn., on May 16, 1907. The blast and its disastrous effect has been described by Mr. Hunter McDonald, M. Am. Soc. C. E., in a paper read before the Engineering Association of the South and reprinted in the Proceedings of the Association for April-June, 1907. The excessive damage was so largely due to coincidence and wreckage of the bridge and train so complete that the incident is worthy of notice.